2009
DOI: 10.1007/s11126-009-9092-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Other Risk Factors for Jail Incarceration Among Male Veterans

Abstract: Data derived from the 2002 Survey of Inmates in Local Jails and the 2000 National Survey of Veterans show that having mental health problems in addition to such sociodemographic characteristics as being a member of a minority group, not being married, having less education, and being younger are risk factors for incarceration among veterans, as they are for the general population. As in previous studies veterans who served during the Vietnam Era and to an even greater extent, those who served in the early year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 31 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…Virtually all identified studies regarding family/marital circumstances were limited to tests of group differences in cross-sectional analyses. For example, relative to nonincarcerated veterans, incarcerated veterans were less likely to be married (Greenberg & Rosenheck, 2009) and were more dissatisfied in their marital relationships (Shaw et al, 1987). In addition, incarcerated veterans reported more problems and lack of support from family members (Benda, Rodell, & Rodell, 2003) and higher rates of spousal abuse perpetration (Gondolf & Foster, 1991).…”
Section: Results: the Moderate Four As Risk Factors For Justice Involmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually all identified studies regarding family/marital circumstances were limited to tests of group differences in cross-sectional analyses. For example, relative to nonincarcerated veterans, incarcerated veterans were less likely to be married (Greenberg & Rosenheck, 2009) and were more dissatisfied in their marital relationships (Shaw et al, 1987). In addition, incarcerated veterans reported more problems and lack of support from family members (Benda, Rodell, & Rodell, 2003) and higher rates of spousal abuse perpetration (Gondolf & Foster, 1991).…”
Section: Results: the Moderate Four As Risk Factors For Justice Involmentioning
confidence: 99%
“…A lower level of education and lack of employment increased the odds of committing crimes among veterans (Benda et al, 2003), and incarcerated veterans were found to have a shorter employment history compared with nonincarcerated veterans (Shaw et al, 1987). Incarcerated veterans were half as likely to have an education beyond high school or a General Education Diploma compared with nonincarcerated veterans, but incarcerated veterans reported higher rates of employment (Greenberg & Rosenheck, 2009). In addition, Rothbard et al (1999) failed to find a significant association between improvements in employment after treatment entry and number of posttreatment arrests among veterans.…”
Section: Results: the Moderate Four As Risk Factors For Justice Involmentioning
confidence: 99%
“…[8][9][10] Apart from the distress and reduced quality of life associated with this disorder, military Veterans with PTSD and their families are often confronted with job loss, 11 poor family functioning, 12 homelessness, 13 anger, violence, 14,15 and incarceration. 16 Approximately 11% of patients served by the Department of Veterans Affairs (VA) healthcare system have been diagnosed with PTSD. 17 Despite this, estimates suggest that up to 40-50% of the Veterans who need and are eligible for mental health services in the United States do not access these services, and many of those who initiate mental healthcare drop out of treatment prematurely.…”
mentioning
confidence: 99%
“…Difficulties with housing are common, as inmates are 7–10 times more likely to be homeless than the general population. 14 Many individuals in jail and prison have low levels of education, with 40% having never completed high school or a GED, 15 and there is a significant overlap between neighborhood poverty and incarceration. Individuals entering prison were earning 41% less prior to incarceration than their non-incarcerated age-matched counterparts.…”
Section: Incarceration In the United Statesmentioning
confidence: 99%